Case series of photic maculopathy associated with exposure to a plasma flash induced by a femtosecond laser. Issue 5 (19th January 2022) - Jiang, Fagang; Shi, Yao; Wang, Zhi; Yang, Xiaobo
Abstract: Background and Objectives: Photic maculopathy resulting from laser‐induced plasma flash has been rarely reported, and the corresponding mechanism of the injury is still unclear. We present a case series of three patients with bilateral macular injuries produced by exposure to the plasma radiation from femtosecond laser tightly focusing. Study Design/Materials and Methods: Funduscopic findings were accompanied mainly by optical coherence tomography (OCT) investigation of the macula during the follow‐up period. Results: All patients shared similar clinical symptoms soon after the initial injury, including reduced visual acuity and central scotomas. It was acutely characterized by foveolar yellowish faceted lesions upon fundus examination. The main OCT finding in the acute stage was a hyper‐reflective area involving all foveolar retinal layers without retinal edema. Repeat OCT evaluation during the latter stages revealed that the retinal changes were reversible, but delineated mild pathology at the outer foveal retina. This retinal structural recovery was accompanied by improvements in visual acuity and central scotomas as well. Conclusions: Prolonged viewing of a plasma flash induced by a focused femtosecond laser without eye protection may produce persistent damage to the retina. We believe that a photochemical process similar to the mechanism of a solar burn or welder's maculopathy may cause retinal damage in this case series.